2019
DOI: 10.5650/jos.ess18228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Pressure Treatment on Interfacial Properties, Structure and Oxidative Stability of Soy Protein Isolate-Stabilized Emulsions

Abstract: Introduction An emulsion is made up with two immiscible liquids, for example, oil and water. One liquid is dispersed as droplets the internal phase or dispersed in the other phase continuous or external phase 1. In food industry, emulsion is very common and it includs two types, milk, cream, salad dressing and mayonnaise are oil-in-water emulsion, margarine and butter are water-in-oil emulsion. Emulsion is a thermodynamic unstable system effected by a variety of physicochemical mechanisms and tends to break do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the stress of 100–120 MPa, decrease in UV absorption intensity and blue‐shift phenomenon of protein samples signified the exposure of tyrosine residues after HPH treatment and the transfer of proteins from a hydrophilic environment to a more hydrophobic environment. Moreover, it also indicated that protein aggregates showed a tendency of re‐aggregation (Chen et al ., 2019). A slight redshift occurred when the pressure was higher than 120 MPa, which was possibly due to the repackaging of tyrosine (Ren et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the stress of 100–120 MPa, decrease in UV absorption intensity and blue‐shift phenomenon of protein samples signified the exposure of tyrosine residues after HPH treatment and the transfer of proteins from a hydrophilic environment to a more hydrophobic environment. Moreover, it also indicated that protein aggregates showed a tendency of re‐aggregation (Chen et al ., 2019). A slight redshift occurred when the pressure was higher than 120 MPa, which was possibly due to the repackaging of tyrosine (Ren et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Both EAI and ESI steadily improved as the homogenization pressure increased, reaching a maximum of 64.63 ± 0.28 m 2 /g and 23.15 ± 0.19 min at 120 MPa, respectively. HPH and the Maillard reaction caused structural unfolding, which yielded greater flexibility and increased spatial site resistance, thus exposing hydrophobic groups contained within the molecule and increasing the lipophilicity of the protein [ 9 ]. Therefore, protein molecules may be quickly and tightly adsorbed at the water/oil interface to form a dense protective barrier that prevents oil droplets from aggregating, thus increasing the protein’s emulsifying abilities [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, controlling the degree of response during the early stages of conjugation is important. The effects of reducing sugar type and treatment method on the degree of the Maillard reaction have been a main focus of research [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al 58 reported that increasing the operating pressure of HPH beyond an optimum value causes the oxidative degradation of oil during emulsification. On increasing the pressure from 1 to 1200 bar (0.1−120 MPa), no major change in the peroxide value was observed, but on further increasing the pressure beyond 1200 bar, the peroxide value increased rapidly.…”
Section: Assessment Of Oxidative Stability Of the Emulsionmentioning
confidence: 99%